Investigation of the Association Between COVID-19 and Hepatitis B Vaccination Among Healthcare Workers: A Cross-Sectional Study in Turkey - Ecin, Seval Müzeyyen; Sandal, Abdulsamet (La Medicina del Lavoro, 2026)
Backgrounds: Vaccination is a cornerstone of public health. While COVID-19 vaccination became globally prioritized during the pandemic, Hepatitis B immunization has remained a mandatory occupational requirement in Turkey, particularly among healthcare workers (HCWs). This study evaluated Hepatitis B immunization and factors associated with COVID-19 vaccination among Turkish HCWs. Methods: A retrospective cross-sectional study was conducted between February 1 and August 15, 2024, at Mersin City Training and Research Hospital. Employees and trainee students who underwent periodic health examinations were included. Participants were grouped as physicians, non-physician HCWs, and non-healthcare professionals. Data included demographics, vaccination history, hematological and biochemical parameters, and clinical characteristics. Logistic regression identified factors associated with COVID-19 vaccination status. Results: Of 4,048 participants, 92.1% received at least one COVID-19 vaccine dose and 90.0% were vaccinated against Hepatitis B. Physicians demonstrated the highest coverage for both vaccines. Male gender (OR=1.37, 95% CI: 1.04–1.80), non-physician HCW status (OR=2.51, 95% CI: 1.33–4.75), non-healthcare professional status (OR=2.99, 95% CI: 1.55–5.77), and behaviorally linked elevated platelet count (OR=1.54, 95% CI: 1.04–2.28) were independently associated with COVID-19 non-vaccination. A prior history of Hepatitis B vaccination showed a strong protective effect against COVID-19 non-vaccination (OR=0.30, 95% CI: 0.23–0.40). Conclusions: Vaccine uptake varied across occupational groups, with physicians achieving the highest rates. Prior compliance with mandatory Hepatitis B vaccination was positively associated with COVID-19 vaccine acceptance, emphasizing the role of previous immunization behavior in new vaccine adoption. Occupational health policies integrating vaccination counseling and follow-up are essential to improve coverage among non-physician HCWs.